Outpatient chemotherapy drug costs and expensive chemotherapy drug use in 340B and Non-340B hospitals: an observational study - Jianhui Hu; David R. Nerenz (BMC Health Services Research)
Abstract Background The 340B Drug Pricing Program has been controversial since its inception in 1992, a major criticism being that 340B hospitals use more outpatient drugs, and more expensive drugs, because of financial incentives to “make money” through the program. The goal of this study was to determine whether characteristics of patients treated at 340B hospitals, and affiliation of hospitals with NCI-designated cancer centers, would explain higher Part B drug costs and use of more expensive chemotherapy drugs. Methods This is an observational study using data from SEER-Medicare and 340B entity database. Fee-for-service Medicare beneficiaries who were first diagnosed with cancer between 1/1/2013 and 12/31/2015 were included. Hospital, patient, and cancer/clinical characteristics were used as predictors of both overall Part B drug costs and use of expensive chemotherapy drugs. Patient characteristics and cancer conditions were compared between those who were treated at 340B and non-340B hospitals, and between those who used and who did not use any expensive chemotherapy treatment. Independent relationships between overall Part B drug costs and patients’ 340B status, and between patients’ use of expensive chemotherapy drug and patients’ 340B status were evaluated in multivariate analyses, using a “stepwise” generalized estimating equation modeling approach. Results We found that patients at 340B hospitals had a somewhat higher chance of using one of the ten expensive chemotherapy drugs, and somewhat higher overall drug costs, but these relationships became non-significant when patient, cancer/clinical factors, and cancer center status were considered. Compared to the reference patients, patients who were treated in an NCI-designated cancer center or a hospital affiliated with such center, who had certain types of cancers (e.g., B-cell), or had advanced-stage disease had a higher chance to use expensive chemotherapy treatment; patients who were older, survived the first 12 months upon diagnosis, had advanced-stage disease, or had more drug claims had higher drug costs. Conclusions Hospital 340B status was not significantly associated with use of more expensive cancer drugs or drug costs once other relevant factors (e.g., cancer center status, advanced-stage disease) were taken into account.